Slamming Analysis on a 35,000 Ton Class of Drillship - Ahmad, Mahasin M.; Djatmiko, Eko B.; Handayanu, Handayanu (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
Slamming is a phenomenon that occurs on floating structures. Drillship as floating structures have slamming when moving at a certain speed which resulted in the movement of relative vertical bow that exceeded full of water of the bow. This paper was performed on the drillship 35000 tons with variants of speed is 7 knots, 12 knots, 13 knots and 14 knots. The first stage taken was the design of the drillship structures by using Maxsurf in order to get lines plan. After the offset data of drillship has been obtained, modeling followed by Hydrostar to get the heave and pitch motion RAO’s from head seas. The result of RAO is used to analyze the relative vertical motion of the bow in the form of RAO as well. That result is used to analysis of structural response by multiplying the wave spectra ITTC/ISSC. From these calculations will be known slamming parameters that can generate the probabilities, intensity and pressure of slamming on the drillship 35000 tons. Probabilities, intensities and pressure of slamming, the maximum occures while the drillship moving on 14 knot of speed, ie. each of 0.483 times, 124.451 times/hour and 492,232 kPa at 15 m of significant wave height.